2023
DOI: 10.1039/d3sc00075c
|View full text |Cite
|
Sign up to set email alerts
|

Atomically well-defined nitrogen doping for cross-plane transport through graphene heterojunctions

Abstract: The nitrogen doping of graphene leads to graphene heterojunctions with a tunable bandgap, suitable for electronics, electrochemical, and sensing applications. However, the microscopic nature and charge transport properties of atomic-level...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…The reduction of the band gap by annulation of the phenyl rings is mainly based on stabilization of the LUMO energies, while HOMO levels are only slightly affected. [30,31] Stabilization of HOMO and LUMO energies of 3 a-c might be due to the improved contribution of the annulated phenyl rings to both frontier molecular orbitals (FMOs). Introduction of nitrogen in 3 b and 3 c leads to further reduction of both HOMO-und LUMO energy levels.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reduction of the band gap by annulation of the phenyl rings is mainly based on stabilization of the LUMO energies, while HOMO levels are only slightly affected. [30,31] Stabilization of HOMO and LUMO energies of 3 a-c might be due to the improved contribution of the annulated phenyl rings to both frontier molecular orbitals (FMOs). Introduction of nitrogen in 3 b and 3 c leads to further reduction of both HOMO-und LUMO energy levels.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, uncyclized compound 4 has an increased bandgap of 3.7 eV (Figure 5; Table 2). The reduction of the band gap by annulation of the phenyl rings is mainly based on stabilization of the LUMO energies, while HOMO levels are only slightly affected [30,31] . Stabilization of HOMO and LUMO energies of 3 a – c might be due to the improved contribution of the annulated phenyl rings to both frontier molecular orbitals (FMOs).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, a spin channel with a long spin lifetime and a long spin diffusion length is needed. Graphene is considered a very promising candidate for long-distance spin transport due to its weak spin-orbit coupling, long spin coherence length, high electrical mobility, and gate-tunable carrier concentration [19][20][21][22][23]. For example, Kamalakar et al demonstrated spin transport in a graphene channel over a channel length of 16 µm with a spin lifetime of 1.2 ns and 6 µm diffusion length at room temperature [24].…”
Section: Introductionmentioning
confidence: 99%